Ablation of Doublecortin-Like Kinase 1 in the Colonic Epithelium Exacerbates Dextran Sulfate Sodium-Induced Colitis. - Dongfeng Qu; Nathaniel Weygant; Randal May; Parthasarathy Chandrakesan; Mohammad Madhoun; Naushad Ali; Sripathi M Sureban; Guangyu An; Michael J Schlosser; Courtney W Houchen (PLoS ONE, 2015)
Doublecortin-like kinase 1 (Dclk1), a microtubule-associated kinase, marks the fifth lineage of intestinal epithelial cells called tuft cells that function as tumor stem cells in Apc mutant models of colon cancer. In order to determine the role of Dclk1 in dextran sulfate sodium (DSS) induced colonic inflammation both intestinal epithelial specific Dclk1 deficient (VillinCre;Dclk1f/f) and control (Dclk1f/f) mice were fed 3% DSS in drinking water for 9 days, allowed to recover for 2 days, and killed. The clinical and histological features of DSS-induced colitis were scored and immunohistochemical, gene expression, pro-inflammatory cytokines/chemokines, and immunoblotting analyses were used to examine epithelial barrier integrity, inflammation, and stem and tuft cell features. In DSS-induced colitis, VillinCre;Dclk1f/f mice demonstrated exacerbated injury including higher clinical colitis scores, increased epithelial barrier permeability, higher levels of pro-inflammatory cytokines and chemokines, decreased levels of Lgr5, and dysregulated Wnt/b-Catenin pathway genes. These results suggest that Dclk1 plays an important role in regulating colonic inflammatory response and colonic epithelial integrity.